Exploring Religious Moderation in Islamic Education: Reflection of the Maja Labo Dahu Nggahi Rawi Pahu Motto in Mbojo Tribal Society - Nurwahidah Nurwahidah; Ahlan Ahlan (JURNAL PENDIDIKAN IPS, 2025)
Religious moderation has become a key concept in addressing the challenges of pluralism and social harmony in the modern world. In Indonesia, where diverse ethnic groups and beliefs coexist, the Mbojo tribal society, located in West Nusa Tenggara, offers a unique perspective on this issue. The Maja Labo Dahu Nggahi Rawi Pahu motto, which emphasizes unity, mutual respect, and collective responsibility, provides a foundation for religious moderation in this community. This research aims to explore the reflection of this motto in the context of Islamic education in Mbojo society and its role in promoting moderation. The study focuses on understanding how Islamic educational practices align with local wisdom and contribute to the cultivation of religious tolerance and harmony. Using a qualitative approach, the research employs field observations, interviews with community leaders, and an analysis of local educational practices to gather insights into the implementation of religious moderation. The findings indicate that the values embedded in Maja Labo Dahu Nggahi Rawi Pahu significantly influence the educational philosophy of the Mbojo community. Islamic education in this context encourages inclusivity, respect for diversity, and the cultivation of a balanced and moderate worldview. The integration of these values in everyday life has proven to be effective in fostering social cohesion, reducing religious intolerance, and promoting peaceful coexistence. This study contributes to the broader discourse on religious moderation and highlights the potential of integrating local wisdom with Islamic education to create a harmonious and inclusive society.